THE LOGICAL PROBLEM OF EVIL IN ISLAM AND CHRISTIANITY: A Comparative Approach in the Thought System of Ibn Sînâ and Richard Swinburne - Zamzami, Mukhammad; HosseiniEskandian, Abdullah; Aabaszadeh, Aabas; Muktafi, Muktafi (State Islamic University North Sumatra, 2021)
Abstract: The study of the ideas of Ibn Sînâ and Richard Swinburne as the pioneers of Islamic philosophy and the West philosophy, and on the other hand, the existing scholastic and ideological differences, is something that can help us to become more familiar with the thoughts of these philosophers and intellectual differences and similarities. In this research, with the analytical method and using the necessary documents, the nature, types, and solutions of evil in the thought of Ibn Sînâ and Swinburne are examined, and also the two philosophers’ thoughts about evil are compared. Both philosophers have considered the existence of evil not in contradiction with the divine attributes, but it is necessary for the acquisition of good, the minimum existence of which is necessary for the best system of creation.Keywords: evil, Ibn Sînâ, Richard Swinburne, Divine attributes, world of creation